My HD Media Pembelajaran pada Masa Pandemic Covid-19 Berbasis Mobile Learning - Kholisho, Yosi Nur; Khairunnisa, Imma Jannati; Fathoni, Ahmad; Uska, Muhammad Zamroni; Jamaludin, Jamaludin (Educate : Jurnal Teknologi Pendidikan, 2022)
The application of online and offline learning certainly requires more innovation to absorb more optimally, one of which is the application of technology as a learning medium. The role of technology today in learning has a considerable influence. Based on the results of interviews with students, it was revealed that students felt bored with the learning process and with reduced offline learning time while students did not have handbooks for studying at home, so that the implementation of learning was less than optimal. Based on these problems, the design of learning media was carried out on My Hope and Dream's English subject for class XI students based on mobile learning. This research aims to develop My HD learning media, find out its feasibility, and look for user responses to My HD products. The method used in this research is Research and Development (R&D). This method is used to produce products and test the feasibility and user response to the resulting product. The data collection instrument used a questionnaire. Based on the results of the expert evaluation of the application material, it is in the Very Appropriate category for use with an average percentage of 85%. Based on media experts, it is in the Very Appropriate category for use with an average percentage of 89%. User responses were obtained from the data collection results using a questionnaire with an average percentage value of 83% in the Very High category